METHODS OF USING CONNOTATIVE LEARNING MATERIALS IN ENGLISH PRACTICAL LESSONS (Web of Teachers: Inderscience Research, 2025)
The main essence of the scientific research is to improve the methods of enriching students' vocabulary with polysemous words of foreign languages during the lesson using connotative material.